Five Feet Traders In The Cross Of Economic History: Five Feet Traders In The Cross Of Economic History - Nur Hadi (el-Jizya: Jurnal Ekonomi Islam, 2018)
Street vendors (PKL) is a form of business that has a high entrepreneurial spirit and is able to compete amid economic competition. The existence of street vendors tends to be motivated by the problem of lack of employment provided by the government, survival efforts, lack of business capital in the formal sector, complicated rules and bureaucracy, temporary work and heredity and profession, making PKL business as an alternative that can be done by the community. Street vendors or in English also called street traders are always included in the informal sector. PKL is a person who trades using a cart or holds his wares on roadside or sidewalks of city streets around shopping centers / shops, markets, recreation / entertainment centers, office centers and education centers, either permanently or half-settled, unofficial status or semi-official and carried out both morning, afternoon, evening and night in order to meet the needs of life by not involving other parties in a binding manner. The term street vendor was first known in the era of the Dutch East Indies, precisely when Governor-General Stanford Raffles came to power. The development of street vendors in the economic history of humankind experienced progress and modernity. Dissatisfaction with government policies related to the allocation of street vendors, gave birth to traders who went to the community directly, which was called the shock market.